2015
DOI: 10.4049/jimmunol.1500839
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer Cells Support Hepatitis B Virus–Mediated CD8+ T Cell Exhaustion via Hepatitis B Core Antigen–TLR2 Interactions in Mice

Abstract: Hepatitis B virus (HBV) persistence is a fundamental process in chronic HBV infection and a key factor in all related liver diseases; however, the mechanisms have yet to be elucidated. We studied the role of TLR2 in HBV persistence using a well-established HBV-carrier mouse model generated by hydrodynamically injecting a phospho–adeno-associated virus/HBV1.2 plasmid into mice. We found that a genetic deficiency in TLR2 improves HBV elimination, whereas activating TLR2 led to more stable HBV persistence, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 42 publications
5
85
0
Order By: Relevance
“…IL-10 can inhibit noncytolytic NK cell function in patients with acute HBV infection (48). In the chronic HBV-persistent model (6 mg plasmid/mouse) used in our laboratory, we previously observed that IL-10 played a key role in maintaining immune tolerance and that IL-10 deficiency or anti-IL-10R treatment resulted in stronger antiviral function of CD8 + T cells (27,49). These data also suggested that Kupffer cellderived IL-10 played a key role in reducing anti-HBV CD8 + T cell responses in an HBV-tolerant model.…”
mentioning
confidence: 99%
“…IL-10 can inhibit noncytolytic NK cell function in patients with acute HBV infection (48). In the chronic HBV-persistent model (6 mg plasmid/mouse) used in our laboratory, we previously observed that IL-10 played a key role in maintaining immune tolerance and that IL-10 deficiency or anti-IL-10R treatment resulted in stronger antiviral function of CD8 + T cells (27,49). These data also suggested that Kupffer cellderived IL-10 played a key role in reducing anti-HBV CD8 + T cell responses in an HBV-tolerant model.…”
mentioning
confidence: 99%
“…Several in vivo studies have found that NK cells, an important type of immune cells that reside in the liver sinusoids, can adhere to sinusoidal endothelial cells and Kupffer cells, therefore exerting its antimetastatic effect [34, 35]. Metastases of hematogenous tumor to the liver can also be inhibited by NKT cells stimulated with recombinant interleukin-12 (IL-12) [36]. Meanwhile, tumor growth in the liver can be inhibited by α -GalCer, inductor of bystander CD8+ CD122+ T cells and tumor-specific cytotoxic CD8+ T cells [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…KCs can be activated by viral antigens via TLR2, resulting in increased IL-10 production [13, 48]. Elevated IL-10 in the liver suppresses the antiviral T cell activation and induce T cell exhaustion [13, 20, 49].…”
Section: Kupffer Cellsmentioning
confidence: 99%
“…KCs can be activated by viral antigens via TLR2, resulting in increased IL-10 production [13, 48]. Elevated IL-10 in the liver suppresses the antiviral T cell activation and induce T cell exhaustion [13, 20, 49]. Importantly, KCs contribute to liver Treg cell-derived IL-10 production [20], and HBV particles also induce TGF-β production by KCs and probably promote Treg cell differentiation [50].…”
Section: Kupffer Cellsmentioning
confidence: 99%